2019
DOI: 10.21660/2019.61.4679
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Utilization of Cu(ii) Modified Liquid Smoke to Inhibit the Activity of White-Rot Fungi (Schizophyllum Commune Fr) in a Pinewood in-Vitro

Abstract: This study aims to examine the possibility of utilizing Cu(II) modified liquid smoke as an antifungal agent against Schizophyllum commune Fr. in a laboratory test. The liquid smoke was obtained through the pyrolysis of oil palm kernel shells at 300°C, 340°C, and 380°C. The analysis of liquid smoke as an antifungal agent was performed using potato dextrose agar (PDA) media and nystatin as positive controls. The white-rot fungi of Schizophyllum commune Fr. were isolated from fungally infected wood and regenerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In the literature, it has been reported that the wood vinegars of different woods or barks obtained via the pyrolysis process exhibit an antifungal effect (Adfa et al 2020, Oramahi et al 2018, Oramahi and Yoshimura 2013. Faisal et al (2019) used copper to modify palm kernel shell wood vinegar at various concentrations (1 %, 2 % and 3 %). Even at the lowest concentration, they found that the copper-modified wood vinegar significantly inhibited growth of the white-rot fungus Schizophyllum commune Fr.…”
Section: Retention Decay Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it has been reported that the wood vinegars of different woods or barks obtained via the pyrolysis process exhibit an antifungal effect (Adfa et al 2020, Oramahi et al 2018, Oramahi and Yoshimura 2013. Faisal et al (2019) used copper to modify palm kernel shell wood vinegar at various concentrations (1 %, 2 % and 3 %). Even at the lowest concentration, they found that the copper-modified wood vinegar significantly inhibited growth of the white-rot fungus Schizophyllum commune Fr.…”
Section: Retention Decay Resultsmentioning
confidence: 99%
“…Adfa et al (2020) used wood vinegar from Cinnamomum parthenoxylon (CP) wood against Schizophyllum commune white-rot fungus and Fomitopsis palustris brown-rot fungus and found that the wood vinegar had a more toxic effect against the white-rot fungus than againstthe brown-rot fungus, and that the wood vinegar at 0,9 % and 1 % concentrations inhibited the development of both fungal species by 100 %. They stated that the wood vinegar exhibited a good antifungal effect and that there were phenolic compounds released during the lignin degradation.It has been reported in the literaturethat the phenolic and acidic acid compounds in wood vinegar have a significant effect on its antifungal properties (Faisal et al 2019, Sulaiman et al 2005, Velmurugan et al 2009, Yahayu et al 2017.…”
Section: Retention Decay Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In hardwood, pyrolysis will produce siringol as the main component, while in softwood, pyrolysis will produce guaiacol and its derivatives reported by Hadi, Nurhayati, Jasni, Yamamoto, & Kamiya (2010). The group of compounds is able to prevent the growth of bacteria and fungi and viruses reported by Faisal, Utari, Hayvia, & Maulana (2019). The advantages of this liquid smoke can be produced commercially, while the advantages of distillation are reducing the content of unneeded PAH (Polycyclic Aromatic Hydrocarbon) compounds such as benzoa pyrene, removing fat and salt reported by Montazeri, Oliveira, Himelbloom, Leigh, & Crapo (2013).…”
Section: Introductionmentioning
confidence: 99%
“…This pyrolysis produces liquid smoke that can be used for preservatives, biopesticides, and rubber coagulants. [15][16][17] Liquid smoke from the pyrolysis of wood materials contains compounds such as phenol, carbonyl, aldehydes, ketones, acetic acid, propionate, butyrate, and valerate.…”
Section: Introductionmentioning
confidence: 99%